TAPBPR isoforms exhibit altered association with MHC class I. Issue 2 (June 2014) - Porter, Keith M.; Hermann, Clemens; Traherne, James A.; Boyle, Louise H.
Summary The tapasin‐related protein TAPBPR is a novel component of the antigen processing and presentation pathway, which binds to MHC class I coupled with β2‐microglobulin. We describe six alternatively spliced TAPBPR transcripts from the TAPBPL gene and investigate three of these at a protein level. TAPBPR transcripts lacking exon 5 result in loss of the membrane proximal IgC domain and loss of ability to bind to MHC class I. Alternative acceptor and donor splice sites in exon 4 of TAPBPR altered the reading frame in the IgV domain and produced a truncated TAPBPR product. An additional exon in the TAPBPL gene was identified that encodes extra residues in the cytoplasmic tail of TAPBPR. This longer TAPBPR protein interacted with MHC class I but was attenuated in its ability to down‐regulate surface expression of MHC class I. The abundance of these alternative transcripts in peripheral blood mononuclear cells and dendritic cells suggests an important role of TAPBPR isoforms in vivo.